Interaction of lipopolysaccharides with plasma high-density lipoprotein in rats. - Freudenberg, M A (1980)
The method of crossed immunoelectrophoresis was used to investigate early changes in plasma proteins of rats treated with lipopolysaccharide (LPS). Intravenous injection of a smooth (S)- and a rough (R)-form preparation led to alterations in the high-density lipoprotein (HDL) precipitation peak. The changes were dose dependent and characteristic for each LPS. The changes were identified as being due to the formation of a complex of LPS with HDL, the complex of the S-form LPS with HDL migrating slower and that of the R-form LPS with HDL migrating faster than free HDL. The fate of the complex was followed in the plasma of injected rats, and it was shown that the R-form LPS complex disappeared after several hours, whereas the S-form LPS complex was still partly present after 2 days. Plasma clearance studies, carried out with 14C-labeled LPS, revealed similar differences in the rate of elimination of the two LPSs. In both cases the time of clearance resembled that of the disappearance of LPS-HDL complex. These results may indicate that HDL represents a transport protein for LPS in plasma to organs of clearance or to other cellular targets.